2011
DOI: 10.1186/1471-2164-12-400
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome and comparative analysis of Streptococcus gallolyticus subsp. gallolyticus, an emerging pathogen of infective endocarditis

Abstract: Background: Streptococcus gallolyticus subsp. gallolyticus is an important causative agent of infectious endocarditis, while the pathogenicity of this species is widely unclear. To gain insight into the pathomechanisms and the underlying genetic elements for lateral gene transfer, we sequenced the entire genome of this pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…These genes encode for a lantibiotic that share high degree of similarity with Smb and haloduracin. Hinse et al (56) have shown that the BAA-2069 strain indeed produces a lantibiotic that is active. Therefore, we tested S. mutans V403, S. sanguinis SK36, and S. pyogenes JRS4 strains overexpressing SmbFT or containing the vector.…”
Section: Resultsmentioning
confidence: 99%
“…These genes encode for a lantibiotic that share high degree of similarity with Smb and haloduracin. Hinse et al (56) have shown that the BAA-2069 strain indeed produces a lantibiotic that is active. Therefore, we tested S. mutans V403, S. sanguinis SK36, and S. pyogenes JRS4 strains overexpressing SmbFT or containing the vector.…”
Section: Resultsmentioning
confidence: 99%
“…AP012053.1), and ATCC BAA-2069 (accession no. FR824043) were compared by using the EDGAR software to identify genes they have in common (20)(21)(22)(23). From the resulting gene pool, a set of 22 housekeeping genes were selected on the basis of the variability and length (Ͼ500 bp) of DNA sequences or usage in other MLST schemes.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, a D test positivity rate of 89% for clindamycin-susceptible, erythromycin-resistant isolates was observed in one study (34), and all S. bovis group isolates in another study exhibited low-level resistance to the aminoglycosides (36). A high percentage of tetracycline resistance reported by Beck et al (9) may be possibly explained by the recent identification of pSGG1, a novel plasmid carrying genes for tetracycline resistance that has strong sequence similarities to plasmids and chromosomes in several ruminal and gastrointestinal bacteria, thus suggesting a potential for horizontal gene transfer (40). Future genomic studies may highlight other potential mechanisms of resistance.…”
Section: Antimicrobial Susceptibilitymentioning
confidence: 96%
“…Several contradictory results have been published in the S. bovis group literature, with unreliable 16S rRNA gene and sodA sequences of type strains deposited in GenBank (9,37). Many anticipate that use of new approaches, such as whole-genome sequencing, may result in another reevaluation of taxonomic status in the future (40). Keeping up to date with these changes and understanding their clinical relevance will be imperative for clinical microbiologists and infectious disease physicians alike.…”
Section: Genomic Analysismentioning
confidence: 99%